Rancang bangun sistem rem anti-lock brake system (abs) dengan penambahan komponen vibrator solenoid - zakaria .; Wibowo .; Wibawa Endra Juwana (Badan Kerja Sama Teknik Mesin Indonesia, 2016)
This study aims to analyze the vibration of the braking system equipped by solenoid vibrator component arranged with a control system to produce an ABS effect. Data collection is done by using slam stick. The results showed that the frequency domain signal with the addition of the solenoid vibrator component had peaks at 10 Hz frequency, while the frequency domain signal during braking without the addition of the solenoid vibrator component there were no peaks at 10 Hz frequency. From the data, the ABS braking system works in accordance with the ABS braking system that provides 10 Hz signal.